Tinjauan Shirkah terhadap Sistem Pay Per Click (PPC) dada Google Adsense dan Facebook - Azzahra, Rahma Hanim (Maliyah : Jurnal Hukum Bisnis Islam, 2022)
This research was conducted to determine the Pay Per Click (PPC) system in collaboration between Google AdSense and Facebook from a Shirkah perspective. This research is field research, with data collection using interviews, observation, and literature review by explaining how the Pay Per Click (PPC) system works in collaboration with Google AdSense and Facebook and then analyzing it according to Islamic law. The results of this study indicate that websites or blogs create Facebook fan page accounts which publishers carry out to promote posting website links or blog links to be accepted as Google AdSense cooperation partners. Ad services will appear randomly to have generated dollars if someone clicks on the ad. The author views the contract between the two parties as valid. However, the advertising services that are displayed randomly contain mutashabihat or ambiguous matters. Because Google itself has many AdWords partners from many types of companies. If publishers can guarantee the appearance of advertising services on their websites or blogs with good educational advertisements, then this collaboration will have no significant problems. If not, the publishers have the role of spreading evil because they have helped the advertisements displayed by Google.